Digital Economy: Technology Acceptance Model Supports Indonesia's Sustainable Economy (Continuance Intention in Generation Z based on Customer Experience using Shopee) - Putri, Nur Latifa Isnaini; Fitria, Novy; Istichomah, Istichomah (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2025)
Data security and privacy are crucial points that must always be reviewed to ensure better data protection in the era of digitalization. How Generation Z can measure readiness and risks is a way to prepare individuals for engaging in online shopping/e-commerce activities. A marketing strategy called postmodern marketing is one of the company's efforts to gauge how Generation Z perceives their experience from using an e-commerce application. The objective of this study is to examine Generation Z's interaction with e-commerce applications in their everyday routines, emphasizing their perceived usefulness, ease of use, and risk. The research employs SEM-PLS to analyze data from questionnaires. The study collected responses from 346 respondents using purposive sampling technique. The results show that the perceived risk can be overlooked when customers feel that the perceived benefits are greater than the anticipated risks. TAM also has a stronger in-fluence when mediated by customer experience.